Prevalence of muscular dystrophy in patients with muscular disorders in Tehran, Iran - Khadijeh Hajinaghi Tehrani; Maliheh Hajiloo; Elham Asadollahi; Fariba Paydar Lagini (PAGEPress Publications, 2018)
Muscular dystrophy is a group of diseases that is characterized by progressive muscle wasting and the weakness of variable distribution and severity. On the basis of the distribution of predominant muscle weakness, there are many different kinds of muscular dystrophy. Some dystrophies are especially frequent in certain populations. There are no studies on the prevalence of muscular dystrophy in Iran. This study was aimed to survey the prevalence of muscular dystrophy among Iranian patients with muscular disorders. This analytical cross-sectional study was conducted on 1000 patients with musculoskeletal disorders who visited the dystrophy association of Bou-Ali Hospital (Tehran) from June 2014 to June 2016. Patients' data were extracted using a checklist that included age, gender, age of onset, family history, findings from clinical diagnostic tests and types of muscular dystrophy. The clinical findings were the results of genetic tests; EMG-NCV; para-clinical findings, including LDH and CPK; and pathological findings. All data were analyzed by SPSS V.22 (IBM Inc., NY) with Chi Square and One way ANOVA tests. All analyses were performed with P = 0.05 considered as the threshold of statistical significant. Out of the 337 patients studied, 262 (77.7%) were male and 75 (22.3%) were female. Subjects had a mean (± SD) age of 26.08 (± 11.86) years with an age range of 3 to 59 years. The most common types of muscular dystrophy were found to be Duchenne dystrophy (131 cases, 38.9%), limb-girdle dystrophy (91 cases, 27%), Becker dystrophy (58 cases, 17.2%), FSHD dystrophy (31 cases, 9.2%), and SMA (26 cases, 7.7%), respectively. The results showed that a statistically significant relationship between dystrophy types and gender, age, family history, age of diagnosis, CPK and LDH levels (P < 0.001). There were no statistical relationship between dystrophy types and pathological findings (P = 0.57), EMG-NCV test results (P = 0.062), and genetic findings (P = 0.06). Since muscular dystrophies often appear during the first decade of life, any information in regard to their prevalence can contribute to better planning and provisioning of required services, as well as better treatment or control of the condition. The results also showed that genetic tests, para-clinical tests, pathology analysis, and EMG-NCV tests can serve as good diagnostic tools for different varieties of dystrophy. Thus, facilitation of these diagnostic tests, particularly the genetic tests, can lead to a faster and more accurate diagnosis of dystrophy, especially in people with a family history of the disease.